Measuring pre-service teachers' Asia literacy and their preparedness to teach Asia. Issue 3 (2nd July 2016) - Grainger, Peter; Christie, Michael
Abstract : Asia literacy is a growing concern of the Federal Government in relation to the development of an Asia literate workforce. Despite 30 years of funded initiatives, the thought of teaching about Asia is a daunting one for pre-service teachers. This is due to the lack of Asia foci in university pre-service courses and complicated by the definition of Asia literacy. This study sought to identify the Asia literacy needs of 54 undergraduate pre-service students in a teacher education programme of study at a regional university. Results of this study indicated that few respondents considered themselves to be Asia literate and most did not believe they were ready to teach about Asia. However, the majority of respondents wanted to know more about Asia prior to graduation. The results indicate that much needs to be done to support students and universities in preparing students to teach about Asia.